'Cryptogenic Drop Attacks' revisited: evidence of overlap with functional neurological disorder. Issue 7 (7th February 2018) - Hoeritzauer, Ingrid; Carson, Alan J; Stone, Jon
Abstract : Objective: In their 1973 BMJ paper 'Cryptogenic Drop Attacks', Stevens and Matthews described 40, mostly middle-aged, female patients with drop attacks of unknown cause. Although clinically common, there has been little on this topic since. We aimed to determine clinical features, comorbidity and outcome of patients with drop attacks. Methods: We carried out a retrospective review of patients with cryptogenic drop attacks seen consecutively by one clinician (JS) between 2006 and 2016. Demographics, phenomenology, duration and frequency of attacks, attack description and comorbid diagnoses were recorded. Patients were followed up with a notes review. Results: 83 patients with cryptogenic drop attacks were predominantly female (89%, n=79), mean age 44 years. The majority (93%, n=77) could not remember the fall itself and almost half (43%, n=36) experienced prodromal dissociative symptoms. Mechanical trips or syncope preceded drop attacks, historically, in 24% (n=20) of cases. Persistent fatigue (73%, n=61), chronic pain (40%, n=33), functional limb weakness (31%, n=26) and dissociative (non-epileptic) attacks 28% (n=23) were common, with the latter usually preceding or emerging from drop attacks. At follow-up (88%, mean 38 months), 28% (n=23) had resolution of their drop attacks. Predisposing (but non-causative) disease comorbidity was found at baseline (n=12) and follow-up (n=5). Conclusions: Cryptogenic drop attacks are associated with high frequency of comorbid functional somatic and functional neurological disorders. Patients commonly have prodromal dissociative symptoms and in some there was a clear relationship with prior or subsequent dissociative (non-epileptic) attacks. Some cryptogenic drop attacks may be best understood as phenomena on the spectrum of dissociative attacks.